EFFECTS OF ORGANIZATIONAL CHANGE ON PERFORMANCE OF THE KENYAN JUDICIARY: A CASE STUDY OF MILIMANI LAW COURTS - (:unkn) unknown (kabarak, 2014)
Following the adoption of the new constitution by the Kenyan Government in the year 2010, the Judiciary undertook a transformation process which was necessitated by the demand by the people of Kenya though the constitution. Kenya’s Judiciary has therefore embarked on massive transformation initiative which includes decentralization of power, structural changes, adopting ICT as an enabler of justice, redefined individual roles, better communication channels and change in leadership who have been publicly vetted. The main objective of this project is to analyze the effects of organizational change on performance of the Kenyan Judiciary since the entry of the current administration in the year 2011. Previous research has not concentrated on the performance of the Judiciary with the new leadership hence this research seeks to bridge that gap in knowledge. The study targeted a population of 1,102, which comprised of 102 senior advocates in Nairobi and 1000 litigants who visited Milimani Law Courts. Systematic sampling was used to sample the litigants whereby 10% represented the population. Questionnaire with closed, multiple choice and open ended questions was used to collect data which was then analyzed using SPSS version 21. The relationship between independent and dependent variables were done through path analysis with independent variables with p<0.01 being excluded. The overall agreement on the positive effect by the structural changes adopted was at 72%, ICT at 74%, organizational communication at 66% and leadership at 61%. The findings demonstrated that the new judicial system has shown an overall transformation in the manner in which Judiciary has been offering its services to the public. The Judiciary should therefore continue to give a special focus on improving organizational performance. I wish to recommend that similar studies be done in other stations outside Nairobi to determine how organizational change in the Judiciary has affected their performance.